An Antireflective Nanostructure Array Fabricated by Nanosilver Colloidal Lithography on a Silicon Substrate - Park Seong-Je; Lee Soon-Won; Lee Ki-Joong; Lee Ji-Hye; Kim Ki-Don; Jeong Jun-Ho; Choi Jun-Hyuk (Nanoscale Research Letters, 2010)
Abstract An alternative method is presented for fabricating an antireflective nanostructure array using nanosilver colloidal lithography. Spin coating was used to produce the multilayered silver nanoparticles, which grew by self-assembly and were transformed into randomly distributed nanosilver islands through the thermodynamic action of dewetting and Oswald ripening. The average size and coverage rate of the islands increased with concentration in the range of 50–90 nm and 40–65%, respectively. The nanosilver islands were critically affected by concentration and spin speed. The effects of these two parameters were investigated, after etching and wet removal of nanosilver residues. The reflection nearly disappeared in the ultraviolet wavelength range and was 17% of the reflection of a bare silicon wafer in the visible range.